Praktik Talak Pada Masyarakat Bangka Belitung Perspektif Fiqh dan Hukum Positiif - Rifdah, Rifdah (Jurnal Ius Constituendum, 2022)
The purpose is to examine the practice of divorce and the validity of oral talaq in the people of Bangka Belitung from the effectiveness of fiqh and positive law by stating the large number of divorce rates without religious court proceedings in Bangka Belitung which caused many riots.  Based on factual data in society which number of divorce rates tends to increase in 2019. It is recorded in the Religious Courts because of divorce outside the provisions of the Compilation of Islamic Law. Talaq is considered legitimate as they know from religious leaders and regional extension workers. This is contrary to positive law whose validity must be carried out through religious court hearings. This research is empirical, through a legal sociology approach, namely how the implementation of the law and the deviation of the rule of law in the Bangka Beliung community because they practice talaq without a religious court process. This study is built on the sadduz-zariah theory which refers to the theory of how to prevent mafadah and reject something that is mubah so as not to lead to something that is forbidden. The study presents three main findings: First, many practices of oral divorce without religious court proceedings in Bangka Belitung. Secondly, many impacts of siri divorce such as siri marriage, domestic violence, abandoned children etc. Third, this researches contribute thoughts in the fiqh and positive legal reviews to the talaq practices of the People of Bangka Belitung. The validity of the Oral Talaq of the Bangka Belitung Community from the perspective of jurisprudence is valid if the conditions and pillars are met while according to positive law it is invalid because it is without a religious court process and has an impact on many mudharatans that are contrary to tasyri'iyyah methods. Therefore, it is necessary to re-enforce criminal regulations and fines for couples who are married or divorced under their hands so as to avoid mudharatan and even realize the maslahah.Penelitian ini mengkaji praktik perceraian dan keabsahan talaq lisan pada masyarakat Bangka Belitung perspektif fiqh dan hukum positif dengan mengemukakan banyaknya angka perceraian tanpa proses pengadilan agama di Bangka Belitung yang menimbulkan banyak kemudharatan. Berdasarkan data faktual di masyarakat bahwa jumlah angka perceraian cenderung meningkat pada tahun 2019. Belum lagi angka yang tidak terdata di Pengadilan Agama karena perceraian di luar ketentuan Kompilasi Hukum Islam. Talaq dianggap sah sebagaimana yang mereka ketahui dari tokoh agama dan penyuluh wilayah. Hal ini bertentangan dengan hukum positif yang keabsahannya harus dilakukan melalui sidang pengadilan agama. Penelitian ini bersifat empiris, dengan pendekatan sosiologi hukum yakni bagaimana implementasi hukum dan terjadi penyimpangan aturan hukum pada masyarakat Bangka Beliung karena mempraktikkan talaq tanpa proses pengadilan agama. Kajian ini dibangun atas sadduz-zariah yang mengacu pada teori tentang bagaimana mencegah mafsadah dan menolak sesuatu yang mubah agar tidak mengantarkan larangan. Tiga temuan utama yakni: Pertama, banyaknya praktik perceraian lisan tanpa proses pengadilan agama di Bangka Belitung. Kedua, banyak dampak perceraian siri seperti nikah siri, kekerasan dalam rumah tangga, anak terlantar dsb. Ketiga, sumbangsih pemikiran dalam tinjauan hukum fiqh dan positif terhadap praktik talaq masyarakat. Keabsahan talaq lisan masyarakat Bangka Belitung menurut perspektif fiqh adalah sah jika syarat dan rukunnya terpenuhi sedangkan menurut hukum positif adalah tidak sah karena tanpa proses pengadilan agama dan berdampak banyak kemudharatan yang bertentangan dengan kaedah-kaedah tasyri iyyah. Oleh karena itu, perlu ditegakkan kembali regulasi pidana maupun denda bagi pasangan yang menikah maupun bercerai di bawah tangan agar terhindarnya kemudharatan bahkan dapat mewujudkan maslahah.